1996
DOI: 10.1128/aem.62.2.735-738.1996
|View full text |Cite
|
Sign up to set email alerts
|

Selective enumeration of Bacteroides vulgatus and B. distasonis organisms in the predominant human fecal flora by using monoclonal antibodies

Abstract: The genus Bacteroides represents about one-third of the isolates from human fecal samples. The proportions of the different species are difficult to estimate because there is no method for rapid identification of mixtures of anaerobes. Monoclonal antibodies against Bacteroides vulgatus and B. distasonis were prepared. They did not react with the other Bacteroides species of the B. fragilis group. These reagents allowed direct enumeration of B. vulgatus and B. distasonis organisms in human fecal samples. Anaero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…It has been found that B. vulgatus was more abundant than the other members in the B. fragilis group in the fecal samples of healthy volunteers using a culture-dependent method (Meijer-Severs & van Santen, 1986). Corthier et al (1996), using monoclonal antibodies, detected B. vulgatus in the fecal samples of 50 healthy adults, and B. vulgatus was found to exist at high levels in most healthy human intestines. Furthermore, they also showed that the population level of B. vulgatus was not influenced by minor environmental variations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that B. vulgatus was more abundant than the other members in the B. fragilis group in the fecal samples of healthy volunteers using a culture-dependent method (Meijer-Severs & van Santen, 1986). Corthier et al (1996), using monoclonal antibodies, detected B. vulgatus in the fecal samples of 50 healthy adults, and B. vulgatus was found to exist at high levels in most healthy human intestines. Furthermore, they also showed that the population level of B. vulgatus was not influenced by minor environmental variations.…”
Section: Discussionmentioning
confidence: 99%
“…For the enumeration of total Bacteroides, dilutions of human faecal samples were plated using brain-heart infusion and exposed to air for 1 h to preselect for non-extremely oxygen-sensitive microorganisms, prior to incubation under strict anaerobic conditions at 37 °C for 48 h (Corthier et al, 1996). Colonies were transferred onto Nytran-Plus membranes (Schleicher and Schuell, Ecquevilly, France) following the manufacturer's recommendations.…”
Section: Microbial Enumerationsmentioning
confidence: 99%
“…Faecal samples were collected, diluted and plated into appropriate agar plates. They were exposed to air for 1 h to preselect for microorganisms that were not extremely oxygen sensitive [20], prior to incubation at 37³C for 3 days under anaerobic conditions in a Freter anaerobic glove box [21]. Antibiotics (Coger and Sigma) were added as required at ¢nal concentrations of 10 Wg ml 3I tetracycline (Tc), 100 Wg ml 3I rifampicin (Rif), 10 Wg ml 3I clindamycin (Cc), 100 Wg ml 3I erythromycin (Em), 140 Wg ml 3I neomycin (Neo), 50 Wg ml 3I Nal, 100 Wg ml 3I streptomycin (Sm), 50 Wg ml 3I kanamycin (Kn) and 25 Wg ml 3I ampicillin (Ap).…”
Section: Bacterial Strains Plasmids and Growth Conditionsmentioning
confidence: 99%